Emerging Research Advancements to Overcome the Peach Spring Frost - Pandiyan Muthuramalingam; Rajendran Jeyasri; Yeonju Park; Seongho Lee; Jae Hoon Jeong; Yunji Shin; Jinwook Kim; Sangmin Jung; Hyunsuk Shin (Research in Plant Disease, 2023)
The phenomena of global warming has led to an increase in the average air temperature in temperate climates. Springtime frost damage is becoming more common, and after a period of dormancy, damage to buds, blooms, and developing fruits is greater significant than damage from low winter temperatures. Peaches are a crucial crop among moderate fruits. Spring frost damage in peaches can have a negative effect on crop growth, yield, and quality. It is noteworthy that these plants have evolved defenses against spring frost damage while being exposed to a variety of low temperatures in the early spring. In this current review, recent research advancements on spring frost damage avoidance in peaches were deliberated. Additionally, adaptive mechanisms of peach, such as deacclimation and reacclimation, were emphasized. Moreover, the emerging advancements using various omics approaches revealed the peach physiology and molecular mechanisms comprehensively. Furthermore, the use of chemical products and understanding the spring frost mechanisms through the use of environmental chamber temperature stimulation and infrared thermography studies were also discussed. This review is essential groundwork and paves the way to derive and design future research for agronomists and horticulturalists to overcome the challenges of spring frost damage avoidance and crop management in these circumstances.